Two choices for the functionalization of silica nanoparticles with gallic acid: characterization of the nanomaterials and their antimicrobial activity against Paenibacillus larvae - Vico, Tamara (2016)
Silica nanoparticles attached to gallic acid were synthesized from 7-nm diameter fumed silica particles by different functionalization methods involving the condensation of hydroxyl or carboxyl groups. The particles were characterized by thermal analyses and UV–vis, FTIR, NMR, and EPR spectroscopies. In comparison to free gallic acid, enhanced stability and increased antimicrobial activity against Paenibacillus larvae were found for the functionalized nanoparticles. Thus, both derivatization strategies result in improved properties of the natural polyphenol as antimicrobial agent for the treatment of honeybee pathologies.